Different antibiotic regimes in men diagnosed with lower urinary tract infection – a retrospective register-based study - Kornfält Isberg, Helena (Scand J Prim Health Care, 2020)
OBJECTIVE: To compare the proportion of therapy failure, recurrence and complications within 30 days after consultation between men diagnosed with lower urinary tract infection (UTI) treated with narrow-spectrum antibiotics (nitrofurantoin or pivmecillinam) and broad-spectrum antibiotics (fluoroquinolones or trimethoprim or trimethoprim/sulfamethoxazole). DESIGN: A retrospective cohort study based on data derived from electronic medical records between January 2012 and December 2015. SETTING: Primary health care and hospital care in five different counties in Sweden. Patients: A total of 16,555 men aged between 18 and 79 years diagnosed with lower UTI. MAIN OUTCOME MEASURES: Treatment with narrow-spectrum antibiotics was compared with broad-spectrum antibiotics regarding therapy failure, recurrence and complications within 30 days. RESULTS: The median age of included men was 65 IQR (51–72) years. Narrow-spectrum antibiotics were prescribed in 8457 (40%) and broad-spectrum antibiotics in 12,667 (60%) cases, respectively. Therapy failure was registered in 192 (0.9%), recurrence in 1277 (6%) and complications in 121 (0.6%) cases. Therapy failure and recurrence were more common in patients treated with narrow-spectrum antibiotics and trimethoprim (p < 0.001), but no such difference could be detected regarding complications. CONCLUSION: There was no difference in incidence of complications within 30 days between men treated with narrow- or broad-spectrum antibiotics. Patients prescribed broad-spectrum antibiotics had lower odds of reconsultation because of therapy failure and recurrence. From current data, treatment with narrow-spectrum antibiotics seems to be an optimal choice regarding preventing complications when treating men with lower UTI. KEY POINTS: Complications such as pyelonephritis and sepsis are uncommon in men diagnosed with lower urinary tract infection treated with antibiotics. There was no difference in incidence of complications among men diagnosed with lower urinary tract infection treated with narrow- or broad-spectrum antibiotics. In spite of higher incidence of therapy failure and recurrence, treatment with narrow-spectrum antibiotics seems to be an optimal choice regarding preventing complications when treating men diagnosed with lower UTI.